Plan de negocio para la creación de una planta purificadora, embotelladora y distribuidora de gua en el cantón Ventanas, año 2013 - 2016. Quevedo - Alvarado Guerrero, Wilson Jefferson (2015)
In this research a business plan for the establishment of purification plant water bottles and distributes developed. In the first chapter the problem of research, development and systematization of the problem, besides the justification of the project and the formulation of objectives with the respective hypotheses defined. In the second chapter the theoretical, conceptual and legal basis of research related to fundamentals market feasibility study, technical, economic and financial develops. In the third chapter the methodology used in the study, in which are the techniques, methods, types, sources of research and sample calculation detailing. In the fourth chapter the results of research is reflected through market research, technical, economic and financial. Finally the conclusions and recommendations which finally came after the completion of the research are presented.